The Landscape of Self-Employment in India: Trends, Constraints and Policy Prescriptions - Farzana Afridi (Institute of Labor Economics (IZA), 2025)
This paper assesses the structure and quality of self-employment in India over a decade. India, historically, has had a much larger share of workers who are self-employed and a smaller proportion of wage and salaried workers. This structure of labour force participation has not shifted much in decades. In recent years, the proportion of self-employed has risen relative to the pre-pandemic era, and much more so for women. At the same time, significant underemployment accompanies low earnings of the self-employed. The paper highlights three key constraints for improving the quality of or transitioning out of self-employment – vocational skilling, access to formal credit and legal support for entrepreneurship. It concludes by discussing the implications of technological change and digitization for self-employment and the need for reforming the legal framework of self-employment in India.
Keywords: J2; J24; J31; 330; quality of work; gender; trends; self-employment; India